7Be detection in the 2021 outburst of RS Oph. Issue 2 (24th September 2022) - Molaro, P; Izzo, L; Selvelli, P; Bonifacio, P; Aydi, E; Cescutti, G; Guido, E; Harvey, E J; Hernanz, M; Della Valle, M
ABSTRACT: The recurrent nova RS Oph underwent a new outburst on 2021 August 8, reaching a visible brightness of V  = 4.8 mag. Observations of the 2021 outburst made with the high-resolution UVES spectrograph at the Kueyen-UT2 telescope at ESO-VLT in Paranal enabled detection of the possible presence of 7 Be newly made in the thermonuclear runaway reactions. The 7 Be yields can be estimated at N ( 7 Be)/ N (H)  = 5.7 × 10 −6, which are close to the lowest yields measured in classical novae so far. 7 Be is short-lived and decays only into 7 Li. By means of a spectrum taken during the nebular phase we estimated an ejected mass of ≈ 1.1 × 10 −5 M⊙, providing an amount of ≈ 4.4 × 10 −10 M⊙ of 7 Li created in the 2021 event. Recurrent novae of the RS Oph type may synthesize slightly lower amounts of 7 Li per event than classical novae, but occur 10 3 times more frequently. The recurrent novae fraction is in the range of 10–30 per cent and they could have contributed to the making of the 7 Li that we observe today. The detection of 7 Be in RS Oph provides further support to the recent suggestion that novae are the most effective source of 7 Li in the Galaxy.